Processamento e caracterização de compósito de fibras de sisal e poliuretano derivado de óleo vegetal - Silva, Zeusa Francisca Souza da (2015)
The use of polymer materials in industry and in various sectors aims to develop material with specific characteristics that can reduce cost and be efficient. One of the disadvantages of materials that are develop and processed in the petrochemical industry are volatile organic compounds (VOC) that are derived from fossils and may causing damage to the environment and users who manipulate them. Na alternative is to replace these materials with ones that are not harmful to human health and the environment. This research investigated the best temperature, time and pressure parameters to develop a biodegradable, renewable and solventfree composite by manual compression. Using natural fibers, specifically the sisal fibre that are non-toxic, low cost and can be easily obtained and the polyurethane derived from castor oil, a resin that presents renewable characteristics and does not present solvents in its chemical composition. The composites were characterized by the following tests: three point bending, infrared spectroscopy, thermogravimetric analysis, UVA and UVC radiation, absorption density and thickness. The condition that indicated the best value in mechanical strength for the preparation of the composite was the sample prepared at 70 °C, 90 minutes and 4 MPa. The sample presented a flexural tension of 83,00 ± 9,28 MPa. The SEM analyses revealed the behavior of the bending test. The good fiber/ matrix adhesion contributed to a high flexural strength.